Diversity of Extremely Halophilic Archaeal and Bacterial Communities from Commercial Salts - Gibtan, Ashagrie; Park, Kyounghee; Woo, Mingyeong; Shin, Jung-Kue; Lee, Dong-Woo; Sohn, Jae Hak; Song, Minjung; Roh, Seong Woon; Lee, Sang-Jae; Lee, Han-Seung (Frontiers in Microbiology, 2017)
Salting is one of the oldest food preservation techniques. However, salt is also the source of living halophilic microorganisms that may affect human health. In order to determine the microbial communities of commercial salts, an investigation were done using amplicon sequencing approach in four commercial salts: Ethiopian Afdera salt (EAS), Ethiopian rock salt (ERS), Korea Jangpan salt (KJS), and Korean Topan salt (KTS). Using domain-specific primers, a region of the 16S rRNA gene was amplified and sequenced using a Roche 454 instrument. The results indicated that these microbial communities contained 48.22–61.4% Bacteria, 37.72–51.26% Archaea, 0.51–0.86% Eukarya, and 0.005–0.009% unclassified reads. Among bacteria, the communities in these salts were dominated by the phyla Proteobacteria, Bacteroidetes, Actinobacteria, and Firmicutes. Of the archaea, 91.58% belonged to the class Halobacteria, whereas the remaining 7.58%, 0.83%, and 0.01% were Nanoarchaea, Methanobacteria, and Thermococci, respectively. This comparison of microbial diversity in salts from two countries showed the presence of many archaeal and bacterial genera that occurred in salt samples from one country but not the other. The bacterial genera Enterobacter and Halovibrio were found only in Korean and Ethiopian salts, respectively. This study indicated the occurrence and diversity of halophilic bacteria and archaea in commercial salts that could be important in the gastrointestinal tract after ingestion.